Randomized placebo-controlled dose-ranging and pharmacodynamics study of roxadustat (FG-4592) to treat anemia in nondialysis-dependent chronic kidney disease (NDD-CKD) patients - Besarab, Anatole; Provenzano, Robert; Hertel, Joachim; Zabaneh, Raja; Klaus, Stephen J.; Lee, Tyson; Leong, Robert; Hemmerich, Stefan; Yu, Kin-Hung Peony; Neff, Thomas B. (Nephrology, dialysis, transplantation, 2015)
Roxadustat (FG-4592) is an oral hypoxia-inducible factor prolyl hydroxylase inhibitor that stimulates erythropoiesis. This Phase 2a study tested efficacy (Hb response) and safety of roxadustat in anemic nondialysis-dependent chronic kidney disease (NDD-CKD) subjects. NDD-CKD subjects with hemoglobin (Hb) ≤11.0 g/dL were sequentially enrolled into four dose cohorts and randomized to roxadustat or placebo two times weekly (BIW) or three times weekly (TIW) for 4 weeks, in an approximate roxadustat:placebo ratio of 3:1. Efficacy was assessed by (i) mean Hb change (ΔHb) from baseline (BL) and (ii) proportion of Hb responders (ΔHb ≥ 1.0 g/dL). Pharmacodynamic evaluation was performed in a subset of subjects. Safety was evaluated by adverse event frequency/severity. Of 116 subjects receiving treatment, 104 completed 4 weeks of dosing and 96 were evaluable for efficacy. BL characteristics for roxadustat and placebo groups were comparable. In roxadustat-treated subjects, Hb levels increased from BL in a dose-related manner in the 0.7, 1.0, 1.5 and 2.0 mg/kg groups. Maximum ΔHb within the first 6 weeks was significantly higher in the 1.5 and 2.0 mg/kg groups than in the placebo subjects. Hb responder rates were dose dependent and ranged from 30% in the 0.7 mg/kg BIW group to 100% in the 2.0 mg/kg BIW and TIW groups versus 13% in placebo. Roxadustat transiently and moderately increased endogenous erythropoietin and reduced hepcidin. Adverse events were similar in the roxadustat and placebo groups. Roxadustat produced dose-dependent increases in blood Hb among anemic NDD-CKD patients in a placebo-controlled trial. Clintrials.gov #NCT00761657.